Exploring the Factors Affecting Health Outcomes among Urban Poor Communities in Bangladesh - Kamal Chakrabarty (PSPP JOURNALS, 2023)
The purpose of this research is to better understand the variables that contribute to poor health in Bangladesh's urban areas. The research combined secondary data analysis with main data gathering techniques like surveys and in-depth interviews. The results indicate that the health outcomes of the urban poor are significantly affected by poor living circumstances, inadequate access to healthcare facilities, and low health literacy. The research concluded that the health of Bangladesh's urban poor could be improved through interventions like health education, community-based healthcare services, and policy changes targeted at addressing social determinants of health. These results stress the need for more efficient interventions to help the urban impoverished overcome barriers to healthcare.